Safety, tolerability, and efficacy of a widely available nusinersen program for Polish children with Spinal Muscular Atrophy. (July 2022) - Kotulska, Katarzyna; Chmielewski, Dariusz; Mazurkiewicz-Bełdzińska, Maria; Tomaszek, Katarzyna; Pierzchlewicz, Katarzyna; Rabczenko, Daniel; Przysło, Łukasz; Biedroń, Agnieszka; Czyżyk, Elżbieta; Steinborn, Barbara; Pietruszewski, Jerzy; Boćkowski, Leszek; et al.
Abstract: Spinal muscular atrophy (SMA) is a devastating neuromuscular disorder with limited treatment options. Nusinersen is the first disease-modifying therapy to treat children and adults with SMA. This study aimed to review the safety, tolerability, and efficacy data of a nusinersen treatment program in Polish children. A total of 298 patients aged from 0 to 18 years were included in the nusinersen treatment program in Poland between March 1 and September 20, 2019. All patients were prospectively followed for at least one year. The mean age at treatment onset was 6.9 years. SMA type 1 symptoms were reported in 127 patients (43.5%), SMA type 2 symptoms in 68 cases (23.3%), and SMA type 3 in 93 patients (31.8%). No patient met the inefficiency criteria defined in the program. One year after treatment initiation, all patients assessed by the CHOP-INTEND scale had improved or remained stable. The mean change in CHOP-INTEND score was an increase of 8.9 points between baseline and after one-year treatment ( p  < 0.001). Except for 2 fatal cases, not related to the treatment, no serious adverse events were reported. The results of our study indicate that treatment with nusinersen is beneficial for children with SMA regardless of their age, baseline functional status, or the number of SMN2 gene copies. Therapy with nusinersen was effective and well tolerated by patients. Highlights: Nusinersen was beneficial for SMA children regardless of their age, functional status, or the number of SMN2 gene copies. The percentage of responding patients increases over time. Better functional status at baseline were associated with better response. In patients assessed in the CHOP-INTEND scale, better response was also associated with younger age of patients.